PERSEPSI CIVITAS AKADEMIKA STAIN PADANGSIDIMPUAN TERHADAP RADIO KOMUNITAS PROXY FM STAIN PADANGSIDIMPUAN SEBAGAI MEDIA DAKWAH - Nasution, Fauziah (TAZKIR: Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2014)
AbstractPerception someone has a significant impact on a person's attitude toward what he perceived, whereas the perception is not always true. Perception is a process that konpleks, which consists of a sensing, process, organization and interpretation. In the context of this study that examined is how the public perception of the existence Padangsidimpuan STAIN campus community radio FM Proxy STAIN Padangsidimpuan as media of dakwah. The background of this research presence in campus-based community radio in STAIN Padangsidimpuan. As a campus-based community broadcaster, the campus community participation in radio broadcasting sustainability has become a "duty". Based on this problem, this research is a descriptive qualitative research. This study concluded that the campus community has a positive perception of the presence Padangsidimpuan STAIN radio as a medium of dakwah. It can be seen from the attitude of the campus community who agree that the radio broadcast format STAIN Padangsidimpuan is radio dakwah, and hope that the presence of this radio as a dakwah radio icon in the TABAGSEL. Although there are many differences opinion comes to remain a community broadcasting institution or commercial broadcasters.Kata kunci: persepsi - radio komunitas proxy fm ? media dakwah